2020
DOI: 10.1186/s12935-020-1156-8
|View full text |Cite
|
Sign up to set email alerts
|

A four-DNA methylation signature as a novel prognostic biomarker for survival of patients with gastric cancer

Abstract: Background: Gastric cancer (GC) is the fifth most frequently diagnosed cancer and the third leading cause of cancerrelated mortality. Lack of prognostic indicators for patient survival hinders GC treatment and survival. Methods and results:Methylation profile data of patients with GC obtained from The Cancer Genome Atlas (TCGA) database were analyzed to identify methylation sites as biomarkers for GC prognosis. The cohort was divided into training and validation sets. Univariate Cox, LASSO regression,and multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…A risk score model based on four genes ( GRID2 , ATG4D , GABARAPL2 , and CXCR4 ) was identified as a potential prognostic biomarker for OS of GC (AUC, 0.671; Qiu et al, 2020 ). Another study suggested a high prognostic accuracy of a four-DNA methylation signature in GC patients (AUC, 0.724; Li et al, 2020 ). A seven-miRNA biomarker panel (miR-10b, miR-223, miR-30a-5p, miR-126, miR-21, miR-338, and let-7a) was established for OS prediction and validated using an independent dataset ( Li et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…A risk score model based on four genes ( GRID2 , ATG4D , GABARAPL2 , and CXCR4 ) was identified as a potential prognostic biomarker for OS of GC (AUC, 0.671; Qiu et al, 2020 ). Another study suggested a high prognostic accuracy of a four-DNA methylation signature in GC patients (AUC, 0.724; Li et al, 2020 ). A seven-miRNA biomarker panel (miR-10b, miR-223, miR-30a-5p, miR-126, miR-21, miR-338, and let-7a) was established for OS prediction and validated using an independent dataset ( Li et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, epigenetic changes such as DNA methylation are reliable and specific cancer biomarkers that can be detected by PCR in blood and other body fluids samples easily obtained through noninvasive approach 13 . In particular, evidence from several studies indicated that the combinations of several DNA methylation markers achieved higher sensitivity and specificity for cancer prognosis compared with individual DNA methylation marker 14 16 . Therefore, in this study, we aimed to develop DNA methylation signature significantly associated with CRC prognosis with univariate and multivariate Cox proportional hazards regression analysis and the ROC analysis based on the genome-wide DNA methylation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is an increasing interest about GC epigenetic events, aiming to better understand GC physiopathology and, more importantly, to find relevant targets for translational medicine. In this context, recent investigations proposed new classifications of GCs based on different epigenetic profiles rather than on somatic alterations subtyping, identifying gene methylation panels able to predict the prognosis of patients and the risk of GC metastasis [ 36 , 37 , 38 ]. In this section, we discuss the main histone and DNA epigenetic modifications characterizing GC, while the role of non-coding RNAs and their potential therapeutic interest in gastrointestinal cancers have been recently reviewed elsewhere [ 39 ].…”
Section: Epigenetics Of Gcmentioning
confidence: 99%